الحماية القانونية من التلوث المائي - فرج حسين فرج الحاسي; صلاح محمد محمود المغربي (The Libyan Journal of Science, 2024)
Given that the aquatic environment is one of the environmental frameworks in which man lives, and because man is an influencing factor for this environment, it is necessary to organize his relationship with it in order to preserve it and prevent any change in it or harm the various organisms that live in this environment in the future. And since the privacy of the water environment and the imminent danger it represents in the event of a change in its natural characteristics, the Libyan legislator has followed many policies in many relevant national laws, all of which aim to protect it, based on his view that the water environment is in continuous and increasing deterioration, either through pollution or exploitation. faulty or corrupt. Through this research, we focus mainly on what is the crime of water environmental pollution in the first requirement, We deal with the definition of water environmental pollution in the first section, and the elements and characteristics of the crime of water pollution in the second section. In the second section, we discuss the policy of the Libyan legislator in protecting the water environment, and shed light on the legal protection of the marine environment in the first section, and the legal protection of groundwater and water bodies in the first section. Section two.